2020
DOI: 10.3390/molecules25225334
|View full text |Cite
|
Sign up to set email alerts
|

Searching Hit Potential Antimicrobials in Natural Compounds Space against Biofilm Formation

Abstract: Biofilms are communities of microorganisms that can colonize biotic and abiotic surfaces and thus play a significant role in the persistence of bacterial infection and resistance to antimicrobial. About 65% and 80% of microbial and chronic infections are associated with biofilm formation, respectively. The increase in infections by multi-resistant bacteria instigates the need for the discovery of novel natural-based drugs that act as inhibitory molecules. The inhibition of diguanylate cyclases (DGCs), the enzy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…The contribution of the explicit water molecules residing inside or around the binding pocket can be considered in the MM-GBSA and MM-PBSA calculations with explicit solvation models [ 14 ]. Entropy calculation using normal mode analysis was not considered due to the high computational cost of the calculation, worse performance, and reduced improvement in the accuracy of MM-GBSA and MM-PBSA in most cases for minimized structures [ 15 , 16 ]. Regarding the results of this study, all calculated binding energies are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The contribution of the explicit water molecules residing inside or around the binding pocket can be considered in the MM-GBSA and MM-PBSA calculations with explicit solvation models [ 14 ]. Entropy calculation using normal mode analysis was not considered due to the high computational cost of the calculation, worse performance, and reduced improvement in the accuracy of MM-GBSA and MM-PBSA in most cases for minimized structures [ 15 , 16 ]. Regarding the results of this study, all calculated binding energies are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…During the production phase, each system was run for a total of 10 ns. The final 2 ns of these simulations were utilized for the MMPBSA calculations, consistent with methodologies utilized in previous work [109,110]. This comprehensive approach helps to ensure a robust exploration of the system's phase space.…”
Section: Molecular Dynamics Configurationmentioning
confidence: 99%
“…Aconitic acid may be an inhibitor of biofilm formation. Pestana-Nobles et al [ 70 ] reported a computational study based on molecular docking and molecular dynamic simulation that screened 224,205 molecules from the natural products ZINC15 database. The results predicted TAA as a possible ligand and inhibitor of the PleD protein involved in bacterial biofilm formation.…”
Section: Biological Roles Of Aconitic Acid With Applications In Biolo...mentioning
confidence: 99%